Kształtowanie się tożsamości w okresie adolescencji a podejmowanie zachowań ryzykownych w obszarze używania alkoholu przez młodzież - Jankowiak, Barbara; Wojtynkiewicz, Ewa (Wydawnictwo Naukowe UAM, 2018)
The adolescence period is a time in which appear some significant adjustments concerning one’s identity. Adolescents, both males and females, have to undertake new forms of behaviour and experiment in order to determine their own place in the society and to find the answer to the question ‘who am I?’. Risk behaviours, including using alcohol by young people during adolescence, are supposed to meet the developmental challenges, bearing in mind personal resources and limitations occurring in the context of the development of an adolescent. The article presents a discussion concerning the meaning of a developing identity in using alcohol by adolescents as well as the proper understanding of teenagers’ identity dilemmas when relevant psychological and pedagogical interventions are chosen.
Personality Moulding During Adolescence and Taking Risk Behaviours in the Context of Using Alcohol by Adolescents
Keywords: adolescence; identity; risk behaviours; adolescents